Interaction-induced stabilization of circular Rydberg atoms - Hezel, Bernd; Mayle, Michael; Schmelcher, Peter (Physical review. A, Atomic, molecular, and optical physics, 2011)
We discuss a candidate solution for the controlled trapping and manipulation of two individual Rydberg atoms by means of a magnetic Ioffe-Pritchard trap that is superimposed by a constant electric field. In such a trap Rydberg atoms experience a permanent electric dipole moment that can be of the order of several hundred debye. The interplay of electric dipolar repulsion and three-dimensional magnetic confinement leads to a well controllable equilibrium configuration with tunable trap frequency and atomic distance. We thoroughly investigate the trapping potentials and analyze the interaction-induced stabilization of two such trapped Rydberg atoms. Possible limitations and collapse scenarios are discussed.